ChemInform Abstract: Synthesis of Biocompatible Polysaccharide Analogues and Their Application to in vivo Optical Tumor Imaging. Issue 36 (September 2015) - Miki, Koji; Kimura, Akinori; Inoue, Tatsuhiro; Matsuoka, Hideki; Harada, Hiroshi; Hiraoka, Masahiro; Ohe, Kouichi
Abstract Polysaccharide analogues having 2‐deoxypsicofuranose as a repeating unit are successfully synthesized by ring‐opening metathesis polymerization of 7‐oxanorbornene‐2, 3‐diol and dihydroxylation.